Preparation and application of refractory energy-saving fused zirconia corundum brick
By adjusting the raw material ratio and process flow, including crushing purification, strong magnetic iron removal and arc furnace melting, combined with casting insulation annealing molding, and using silicon sol, the problems of high energy consumption and insufficient performance during the preparation of electromelted zirconium corundum bricks are solved. , realizes the preparation of high-performance refractory and energy-saving electric melted zirconium corundum bricks, improves its refractory and flexural strength, and reduces costs.
Patent Information
- Application Number
- CN202411518570.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electromelted zirconium corundum bricks consume high energy during the preparation process, and the raw material utilization rate is not high, resulting in increased costs, and insufficient refractory, compressive strength and flexural strength, making it difficult to meet the needs of high temperature, high pressure and corrosive environments. need.
By adjusting the raw material ratio, adding sodium polysulfonate, rare earth oxides and boric acid, pulverizing, strong magnetic iron removal and arc furnace melting, combined with casting insulation annealing molding process, silicon sol is used to improve binding strength and reduce porosity. Prepare high-performance refractory and energy-saving electric melted zirconium corundum bricks.
Reduces energy consumption during the preparation process, improves the refractory performance, flexural strength and compressive strength of zirconium corundum bricks, extends product life, reduces maintenance and replacement costs, and significantly improves its in high temperature and corrosive environments. Service life.
Smart Images

Figure BDA0005107401350000071 
Figure BDA0005107401350000081 
Figure BDA0005107401350000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to the preparation and application of a refractory energy-saving fused zirconium corundum brick. Background Art
[0002] With the development of modern industry, the requirements for refractory materials are getting higher and higher, especially in high temperature, high pressure and corrosive environments, traditional refractory materials are often difficult to meet the needs. Therefore, it is particularly important to develop a new type of refractory material that has both excellent refractory properties and energy-saving characteristics. As a high-performance refractory material, fused zirconium corundum bricks have broad application prospects. However, the existing fused zirconium corundum bricks have high energy consumption in the preparation process, and the utilization rate of some raw materials is not high, resulting in increased costs. Therefore, the present invention aims to provide a preparation method and application of refractory and energy-saving fused zirconium corundum bricks to reduce energy consumption in the preparation process, improve raw material utilization, and further improve the product's refractory, compressive strength, flexural strength and other properties. Summary of the invention
[0003] To solve the above problems, the present invention discloses a preparation method and application of a refractory and energy-saving fused zirconium corundum brick. The finished product has high compressive strength, high flexural strength, high load softening temperature, low porosity and moderate density. The raw material utilization rate is high and the energy consumption is low during the preparation process.
[0004] A method for preparing a refractory energy-saving capacitor zirconium corundum brick, characterized in that it comprises the following steps:
[0005] S1. Crushing and purifying raw materials: crushing and grinding zircon sand, high-purity alumina, potassium carbonate, fused magnesia-alumina spinel, silicon nitride and sodium polysulfonate respectively to obtain corresponding powders; adding zircon sand, regenerated fused zirconium corundum brick and fused magnesia-alumina spinel powder to re-distilled water to carry out strong magnetic iron removal, and drying after the strong magnetic iron removal is completed to finally obtain high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesia-alumina spinel powder;
[0006] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then rare earth oxide powder is added to the electric arc furnace, and then boric acid is added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted to obtain a mixed solution after the melting is completed;
[0007] S3 pouring, heat preservation and annealing: the mixed solution obtained in step S2 begins to cool down, and when it drops to 1900-2000°C, silica sol is added to the mixed solution and stirred evenly, and then heat-preserved in this temperature range. After the heat preservation is completed, a pouring liquid is obtained, and the mixed solution is poured into a mold. The temperature and flow rate of the pouring liquid are controlled. After the pouring is completed, the mold is cooled and annealed to obtain a zirconium corundum brick.
[0008] Preferably, in the S1 raw material crushing and purification step, the weight parts of each raw material are: 45-65 parts of zircon sand, 3-8 parts of high-purity alumina, 2-5 parts of potassium carbonate, 12-15 parts of fused magnesia alumina spinel, 1-2 parts of silicon nitride, and 2-3 parts of sodium polysulfonate.
[0009] Preferably, in the step of crushing and purifying the raw material in S1, the mesh size of the sieve used in the crushing and screening process is 200 to 300 meshes.
[0010] Preferably, in the S1 raw material crushing and purification step, the voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 230-280V; and the drying temperature of the drying box during the drying process is 50-80°C.
[0011] Preferably, in the S2 arc furnace melting step, the weight portion of the rare earth oxide is 0.5 to 1.0 parts. The weight portion of the boric acid is 4 to 6 parts.
[0012] Preferably, in the S2 arc furnace melting step, the weight portion of boric acid is 4 to 6 parts.
[0013] Preferably, in the S2 arc furnace melting step, the heating and melting temperature is 2500-3200°C.
[0014] Preferably, in the pouring, heat preservation, annealing and molding step S3, the weight portion of silica sol added is 2 to 3 parts; after the silica sol is added, the mixture is kept warm and stirred for 1 to 2 hours.
[0015] Preferably, in the pouring, heat preservation and annealing molding step S3, the temperature of the pouring liquid needs to be controlled at 1500-1700° C.; the flow rate of the pouring liquid is 1.5-2.0 m / min.
[0016] Preferably, in the pouring, heat preservation and annealing molding step S3, the temperature of the pouring liquid needs to be controlled at 1500-1700° C.; the flow rate of the pouring liquid is 1.5-2.0 m / min.
[0017] A refractory energy-saving capacitor zirconium corundum brick. The zirconium corundum brick prepared by any of the above-mentioned preparation methods of refractory energy-saving capacitor zirconium corundum bricks can be used as lining materials for glass industry pools, furnace pools used in metallurgy, and reactors and heaters in the chemical industry.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a method for preparing a fire-resistant energy-saving capacitor zirconium corundum brick, which adjusts the ratio and components of the raw materials so that the refractory performance of the finished zirconium corundum brick is better. The addition of sodium polysulfonate to the raw materials can reduce the coagulation time of the subsequent pouring liquid; the raw materials are crushed, filtered and strongly magnetically deironed, and the raw materials are further purified to remove impurity particles such as iron, manganese, and organic matter, which can effectively avoid the influence of impurities on the quality of the finished product, extend the service life of the product, and reduce the cost of maintenance and replacement. Adding rare earth oxides in the S2 arc furnace melting step can reduce cracks in the finished zirconium corundum brick and improve the yield of zirconium corundum brick. In the S3 pouring, insulation and annealing molding step, the mixed liquid is cooled to 1900-2000°C, and then silica sol is added and stirred for a period of time. This is because silica sol can help the raw materials increase the bonding strength, reduce the demoulding strength of the casting liquid, increase the refractory temperature, and increase the flexural strength and compressive strength; after adding, the mixture is stirred for a period of time because it can make the casting liquid basically free of open pores, which will significantly reduce the intrusion of foreign objects into the interior of the zircon corundum brick, and greatly improve the corrosion resistance of the zircon corundum brick. DETAILED DESCRIPTION
[0020] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0021] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0022] Example 1: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0023] S1 Raw material crushing and purification: 45 parts of zircon sand, 3 parts of high-purity alumina, 2 parts of potassium carbonate, 12 parts of fused magnesium aluminum spinel, 1 part of silicon nitride and 2 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 200 meshes; the powders of zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 230V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 50°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0024] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then 0.5 parts of rare earth oxide powder is added to the electric arc furnace, and then 4 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted at a temperature of 2500°C. After the melting is completed, a mixed solution is obtained;
[0025] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000℃, add 2 parts of silica sol to the mixed solution, stir evenly and keep it warm in this temperature range for 1h. After the heat preservation, obtain the pouring liquid, pour the mixed solution into the model, control the temperature of the pouring liquid to 1500℃, and the pouring flow rate of the pouring liquid to 1.5m / min. After the pouring is completed, cool the model for annealing, the annealing starting temperature is 1500℃, then cool to 500-650℃ at a rate of 60-90℃ / h, and finally cool naturally to room temperature to obtain zirconium corundum bricks.
[0026] Embodiment 2: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0027] S1 Raw material crushing and purification: 48 parts of zircon sand, 4 parts of high-purity alumina, 3 parts of potassium carbonate, 12.5 parts of fused magnesium aluminum spinel, 1.2 parts of silicon nitride and 2.2 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 220 meshes; the powders of zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 240V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 60°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0028] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then 0.6 parts of rare earth oxide powder is added to the electric arc furnace, and then 4.5 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted at a temperature of 2650°C. After the melting is completed, a mixed solution is obtained;
[0029] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000°C, add 2.2 parts of silica sol to the mixed solution, stir evenly and keep warm in this temperature range for 1.2h. After the heat preservation, obtain the pouring liquid, pour the mixed solution into the model, control the temperature of the pouring liquid to 1550°C, and the pouring flow rate of the pouring liquid to 1.6m / min. After the pouring is completed, cool the model for annealing, the annealing starting temperature is 1550°C, and then cool to 500-650°C at a rate of 60-90°C / h, and finally cool naturally to room temperature to obtain zirconium corundum bricks.
[0030] Embodiment 3: A method for preparing a fire-resistant energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0031] S1 Raw material crushing and purification: 53 parts of zircon sand, 5 parts of high-purity alumina, 3.5 parts of potassium carbonate, 13 parts of fused magnesium aluminum spinel, 1.4 parts of silicon nitride and 2.4 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 240 meshes; the powders of zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 250V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 65°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0032] S2 arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of the raw materials obtained in step S1 are added to the arc furnace in sequence, and then 0.7 parts of rare earth oxide powder is added to the arc furnace, and then 5 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the arc furnace is heated and melted at a temperature of 2800°C. After the melting is completed, a mixed solution is obtained;
[0033] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000℃, add 2.4 parts of silica sol to the mixed solution, stir evenly and keep it warm in this temperature range for 1.4h. After the heat preservation, obtain the pouring liquid, pour the mixed solution into the model, control the temperature of the pouring liquid to 1600℃, and the pouring flow rate of the pouring liquid to 1.7m / min. After the pouring is completed, cool the model for annealing, the annealing starting temperature is 1600℃, then cool to 500-650℃ at a rate of 60-90℃ / h, and finally cool naturally to room temperature to obtain zirconium corundum bricks.
[0034] Example 4: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0035] S1 Raw material crushing and purification: 56 parts of zircon sand, 6 parts of high-purity alumina, 4 parts of potassium carbonate, 14 parts of fused magnesium aluminum spinel, 1.6 parts of silicon nitride and 2.6 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 260 mesh; zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel powder are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 260V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 70°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0036] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then 0.8 parts of rare earth oxide powder is added to the electric arc furnace, and then 5.5 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted at a temperature of 2950°C. After the melting is completed, a mixed solution is obtained;
[0037] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000°C, add 2.6 parts of silica sol to the mixed solution, stir evenly and keep warm in this temperature range for 1.6 hours. After the heat preservation, obtain the pouring liquid, pour the mixed solution into the model, control the temperature of the pouring liquid to 1650°C, and the pouring flow rate of the pouring liquid to 1.8m / min. After the pouring is completed, cool the model for annealing, the annealing starting temperature is 1650°C, and then cool to 500-650°C at a rate of 60-90°C / h, and finally cool naturally to room temperature to obtain zirconium corundum bricks.
[0038] Example 5: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0039] S1 Raw material crushing and purification: 60 parts of zircon sand, 7 parts of high-purity alumina, 4.5 parts of potassium carbonate, 14.5 parts of fused magnesium aluminum spinel, 1.8 parts of silicon nitride and 2.8 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 280 meshes; zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel powder are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 270V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 75°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0040] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then 0.9 parts of rare earth oxide powder is added to the electric arc furnace, and then 6 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted at a temperature of 3100°C. After the melting is completed, a mixed solution is obtained;
[0041] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000℃, add 2.8 parts of silica sol to the mixed solution, stir evenly and keep warm in this temperature range for 1.8h. After the heat preservation, obtain the casting solution, pour the mixed solution into the model, control the temperature of the casting solution to 1700℃, and the casting flow rate of the casting solution to 1.9m / min. After the casting is completed, cool the model for annealing, the annealing starting temperature is 1700℃, then cool to 500-650℃ at a rate of 60-90℃ / h, and finally cool naturally to room temperature to obtain zirconium corundum bricks.
[0042] Example 6: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, comprising the following process steps:
[0043] S1 Raw material crushing and purification: 65 parts of zircon sand, 8 parts of high-purity alumina, 5 parts of potassium carbonate, 15 parts of fused magnesium aluminum spinel, 2 parts of silicon nitride and 3 parts of sodium polysulfonate are crushed, ground and sieved to obtain corresponding powders. The mesh size of the sieve used in the crushing and sieving process is 300 meshes; zircon sand, regenerated fused zirconium corundum brick and fused magnesium aluminum spinel powder are added to re-distilled water for strong magnetic iron removal. The voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 280V; after the strong magnetic iron removal is completed, it is dried. The drying temperature of the drying box during the drying process is 80°C. Finally, high-purity zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesium aluminum spinel powder are obtained;
[0044] S2 electric arc furnace melting: the high-purity zircon sand powder, high-purity regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, high-purity fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of each raw material obtained in step S1 are added to the electric arc furnace in sequence, and then 1 part of rare earth oxide powder is added to the electric arc furnace, and then 6 parts of boric acid are added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the electric arc furnace is heated and melted at a temperature of 3200°C. After the melting is completed, a mixed solution is obtained;
[0045] S3 pouring, heat preservation and annealing: start cooling the mixed solution obtained in step S2 to 1900-2000℃, add 2.8 parts of silica sol to the mixed solution, stir evenly and keep it warm in this temperature range for 1.8h. After the heat preservation, get the pouring liquid, pour the mixed solution into the model, control the temperature of the pouring liquid to 1700℃, pouring flow rate of the pouring liquid to 2.0m / min, after the pouring is completed, cool the model for annealing, the annealing starting temperature is 1700℃, then cool to 500-650℃ at a rate of 60-90℃ / h, finally cool naturally to room temperature to get zirconium corundum bricks.
[0046] Comparative Example 1: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, wherein no sodium polysulfonate is added to the raw materials, and the remaining steps and reaction conditions are the same as those in Example 4.
[0047] Comparative Example 2: A method for preparing a refractory energy-saving capacitor zirconium corundum brick, wherein the raw materials are not subjected to a strong magnetic iron removal purification process, and the remaining steps and reaction conditions are the same as those in Example 4.
[0048] Comparative Example 3: A method for preparing a refractory and energy-saving capacitor zirconium corundum brick, wherein no rare earth oxide is added in the S2 arc furnace melting step, and the remaining steps and reaction conditions are the same as those in Example 4.
[0049] Comparative Example 4: A method for preparing a refractory and energy-saving capacitor zirconium corundum brick, wherein no silica sol is added in the S3 pouring, insulation and annealing molding step, but a cooling and insulation stage is performed, and the remaining steps and reaction conditions are the same as those in Example 4.
[0050] Comparative Example 5: A method for preparing a refractory and energy-saving capacitor zirconium corundum brick, wherein silica sol is added to the S3 pouring, insulation and annealing molding step but no cooling and insulation stage is performed, and after the addition is completed, the temperature is directly lowered to 1650°C for pouring, and the remaining steps and reaction conditions are the same as those in Example 4.
[0051] Comparative Example 6: A method for preparing a refractory and energy-saving capacitor zirconium corundum brick, in which no silica sol is added and no cooling and insulation stage is performed in the S3 pouring, insulation and annealing molding step, the mixed liquid is directly cooled to 1650°C for pouring, and the remaining steps and reaction conditions are the same as those in Example 4.
[0052] Table 1
[0053] Example 1 2 3 4 5 6 Setting time (h) 2.5 2.3 1.9 1.5 1.6 1.7
[0054] Table 2
[0055] Comparative Example 1 2 3 4 5 6 Setting time (h) 3.3 2.3 2.2 2.6 2.5 2.7
[0056] Tables 1 and 2 respectively record the setting time of Examples 1 to 6 and Comparative Examples 1 to 6 in S3 pouring, insulation and annealing. It can be seen from the above recorded data that the setting time of the examples is shorter than that of the comparative examples, the setting time of Example 4 is the shortest, and the setting time of Comparative Example 1 is relatively the longest, which shows that adding sodium polysulfonate to the raw materials can effectively shorten the setting time of zirconium corundum bricks, thereby shortening the production time and reducing production energy consumption.
[0057] The compressive strength, flexural strength, load softening temperature, porosity and density of the zirconium corundum bricks prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested, and the test results are shown in the following table:
[0058] Table 3
[0059]
[0060]
[0061] As shown in the above table, the zirconium corundum bricks prepared in Examples 1 to 6 have high compressive strength, high flexural strength, high load softening temperature, low porosity and moderate density, among which Example 4 has the best performance.
[0062] Compared with Example 4, in Comparative Example 2, in the S1 raw material crushing and purification step, no strong magnetic iron removal is performed on the raw material; in Comparative Example 3, no rare earth oxide is added in the S2 arc furnace melting step; in Comparative Example 4, in the S3 pouring, insulation, annealing and molding step, no silica sol is added during the cooling and insulation stage; in Comparative Example 5, in the S3 pouring, insulation, annealing and molding step, casting is directly performed without insulation after adding silica sol; in Comparative Example 6, in the S3 pouring, insulation, annealing and molding step, neither silica sol is added nor cooling and insulation is performed, and the mixed liquid obtained in the S2 step is directly poured into the mold for cooling and annealing molding. From the test data in Table 3, it can be seen that the various properties of the finished zirconium corundum bricks prepared in Comparative Examples 1 to 6 are worse than those in Example 4. This is because the strong magnetic iron removal step can further purify the raw materials, remove impurity particles such as iron, manganese, and organic matter, and effectively avoid the influence of impurities on the quality of the finished products; rare earth oxides can reduce cracks in the finished zirconium corundum bricks; silica sol can help the raw materials increase the bonding strength. After adding silica sol, keeping warm and stirring for a period of time can still make the casting liquid basically free of open pores, reduce the demoulding strength of the casting liquid, increase the refractory temperature, and increase the flexural strength and compressive strength.
[0063] The finished zirconium corundum bricks prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were used as lining materials in glass industry pools, furnace pools used in metallurgy, reactors and heaters in the chemical industry to prepare new glass industry pools, furnace pools used in metallurgy, reactors and heaters in the chemical industry, and the new products were immersed in a strong acid solution at a temperature of 1500°C to test their corrosion resistance. The test data are shown in Table 4.
[0064] Table 4
[0065]
[0066]
[0067] It can be seen from Table 4 that the corrosion resistance of the new zirconium corundum bricks prepared using Examples 1 to 6 is better than that of the comparative examples, among which the corrosion resistance of the new products of Comparative Examples 5 and 6 is poor. This is because Comparative Examples 5 and 6 do not have a cooling, insulation and stirring step in the S3 pouring, insulation, annealing and molding step, which makes the porosity of the final zirconium corundum bricks large, so the radiation protection performance will be reduced.
[0068] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing refractory energy-saving capacitor zirconium corundum bricks, characterized in that: The process steps include: S1. Crushing and purifying raw materials: crushing and grinding zircon sand, high-purity alumina, potassium carbonate, fused magnesia-alumina spinel, silicon nitride and sodium polysulfonate respectively to obtain corresponding powders; adding zircon sand, regenerated fused zirconium corundum brick and fused magnesia-alumina spinel powder to re-distilled water to perform strong magnetic iron removal, and drying after the strong magnetic iron removal is completed to finally obtain zircon sand powder, regenerated fused zirconium corundum brick powder and fused magnesia-alumina spinel powder; S2 arc furnace melting: the zircon sand powder, regenerated fused zirconium corundum brick powder, high-purity alumina powder, potassium carbonate powder, fused magnesium aluminum spinel powder, silicon nitride powder, and sodium polysulfonate powder of the raw materials obtained in step S1 are added to the arc furnace in sequence, and then rare earth oxide powder is added to the arc furnace, and then boric acid is added. After all the additions are completed, the mixture is stirred and mixed to obtain a mixture, and then the arc furnace is heated and melted to obtain a mixed solution after the melting is completed; S3 pouring, heat preservation and annealing: the mixed solution obtained in step S2 begins to cool down, and when it drops to 1900-2000°C, silica sol is added to the mixed solution and stirred evenly, and then heat-preserved in this temperature range. After the heat preservation is completed, a pouring liquid is obtained, and the mixed solution is poured into a mold. The temperature and flow rate of the pouring liquid are controlled. After the pouring is completed, the mold is cooled and annealed to obtain a zirconium corundum brick.
2. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S1 raw material crushing and purification step, the weight parts of the raw materials are: 45-65 parts of zircon sand, 3-8 parts of high-purity alumina, 2-5 parts of potassium carbonate, 12-15 parts of fused magnesium aluminum spinel, 1-2 parts of silicon nitride, and 2-3 parts of sodium polysulfonate.
3. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S1 raw material crushing and purification step, the mesh size of the sieve used in the crushing and screening process is 200 to 300 meshes.
4. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S1 raw material crushing and purification step, the voltage of the strong magnetic iron remover during the strong magnetic iron removal process is 230-280V; the drying temperature of the drying box during the drying process is 50-80°C.
5. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S2 arc furnace melting step, the weight portion of the rare earth oxide is 0.5 to 1.0 parts.
6. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S2 arc furnace melting step, the weight portion of the boric acid is 4 to 6 parts.
7. The method for preparing a fire-resistant energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S2 arc furnace melting step, the heating and melting temperature is 2500-3200°C.
8. The method for preparing a fire-resistant energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the step S3 of pouring, heat preservation and annealing, the weight of the added silica sol is 2 to 3 parts; after the silica sol is added, the mixture is kept warm and stirred for 1 to 2 hours.
9. The method for preparing a refractory energy-saving capacitor zirconium corundum brick according to claim 1, characterized in that: In the S3 pouring, heat preservation, annealing and molding step, the temperature of the pouring liquid must be controlled at 1500-1700° C.; the flow rate of the pouring liquid is 1.5-2.0 m / min.
10. The zirconia corundum bricks prepared by the method for preparing a refractory energy-saving capacitor zirconia corundum brick as claimed in any one of claims 1 to 9 are used as lining materials for glass industry pools, furnace pools used in metallurgy, or reactors and heaters in the chemical industry.
Citation Information
Patent Citations
Electromelted refractory material
CA916738A
Preparation method of zirconium oxide-enhanced aluminum oxide porous ceramic with closed-pore structure
CN106830961A
High-purity corundum castable prepared by self-initiated solidification molding
CN111187091A
Fused zirconia-corundum brick and preparation method thereof
CN112062549A
Process for producing electric smelting zirconium corundum 33#, 36#, 41# products by secondary casting
CN1693275A